2012
DOI: 10.1105/tpc.112.098640
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Signaling Negatively Regulates Freezing Tolerance by Repressing Expression of CBF and Type-A ARR Genes in Arabidopsis

Abstract: The phytohormone ethylene regulates multiple aspects of plant growth and development and responses to environmental stress. However, the exact role of ethylene in freezing stress remains unclear. Here, we report that ethylene negatively regulates plant responses to freezing stress in Arabidopsis thaliana. Freezing tolerance was decreased in ethylene overproducer1 and by the application of the ethylene precursor 1-aminocyclopropane-1-carboxylic acid but increased by the addition of the ethylene biosynthesis inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
473
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 589 publications
(512 citation statements)
references
References 85 publications
15
473
2
3
Order By: Relevance
“…Briefly, 5-week-old whole plants grown in a soil:vermiculite (1:2, v/v) mixture with or without cold acclimation were subsequently placed in a freezing chamber (RuMED4001; Shi et al, 2012) that was set to maintain a temperature of 0°C for 1 h. The temperature was then decreased at a rate of 1°C h 21 in the dark. The plants were maintained for 1 h at the designated temperature from 22°C to 29°C and transferred to 4°C overnight, then transferred back to 22°C with light (16-h daylength).…”
Section: Freezing Tolerance and Electrolyte Leakage Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 5-week-old whole plants grown in a soil:vermiculite (1:2, v/v) mixture with or without cold acclimation were subsequently placed in a freezing chamber (RuMED4001; Shi et al, 2012) that was set to maintain a temperature of 0°C for 1 h. The temperature was then decreased at a rate of 1°C h 21 in the dark. The plants were maintained for 1 h at the designated temperature from 22°C to 29°C and transferred to 4°C overnight, then transferred back to 22°C with light (16-h daylength).…”
Section: Freezing Tolerance and Electrolyte Leakage Assaysmentioning
confidence: 99%
“…In addition, OST1, a protein kinase involved in abscisic acid (ABA) signaling, phosphorylates and stabilizes ICE1 and suppresses HOS1-mediated ICE1 degradation, thus positively regulating CBFs (Ding et al, 2015). Finally, ethylene represses AtCBF1 to AtCBF3 expression via EIN3 (Shi et al, 2012).…”
mentioning
confidence: 99%
“…Unlike the signal molecules JAs and ethylene, which show immediate accumulation during cold acclimation in Arabidopsis, the contents of free and conjugated SA increase only after one week of treatment. [24][25][26][27] Our recent work further revealed that the levels of SA were significantly increased upon freezing and during the recovery phase after freezing treatment in the wild-type plants, which elevations were absent in the freezing-tolerant sag101, eds1 and pad4 mutants. 18 These findings demonstrate that SAG101, EDS1-and PAD4-mediated SA signaling may contribute to freezing tolerance through a novel mechanism different from the conventional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, overexpression of type-A ARABIDOPSIS RESPONSE REGULATORS (ARR) genes, ARR5, ARR7 and ARR15, confers enhanced freezing tolerance in Arabidopsis. 24 A recent investigation further suggests that the transcript and protein levels of ARRs are down-regulated by supplying with the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC), indicating that the type-A ARRs may be key factors in integrating ethylene and cytokinin pathways in plant responses to cold stresses. 24 Due to the frequent cross-talks between the ethylene and SA pathways, it is necessary to test the effects of SA on the regulation of cold-responsive expression of ARR genes as well as their expression patterns in the freezing-tolerant sag101, eds1 and pad4 mutants.…”
Section: Role Of Sag101 Eds1 and Pad4 In Freezing Tolerancementioning
confidence: 99%
“…1) the activities of hormones such as auxin, ethylene, cytokinin, abscisic acid, gibberellin and brassinosteroids depend on cellular context and exhibit either synergistic or antagonistic interactions (Garay-Arroyo et al, 2012); 2) cellular patterning in the Arabidopsis root is coordinated via a localized auxin concentration maximum in the root tip, requiring the regulated expression of specific genes (Sabatini et al, 1999); 3) auxin is directionally transported through plant tissues, providing positional and vectorial information during development (Vanneste and Friml, 2009;Adamowski and Friml, 2015); 4) auxin concentration and the associated regulatory and target genes are regulated by diverse interacting hormones and gene expression and therefore cannot change independently of the various crosstalk components in space and time (Garay-Arroyo et al, 2012); 5) other hormone concentrations, such as ethylene and cytokinin concentrations, and expression of the associated regulatory and target genes are also interlinked (e.g. To et al, 2004;Shi et al, 2012); and 6) transport of other hormones, such as cytokinin, from the shoot to the root in the phloem (Bishopp et al, 2011;Schaller et al, 2015) in combination with local biosynthesis, degradation and diffusion, could also be an important factor affecting the interaction of hormones and gene expression in Arabidopsis root development.…”
Section: Introductionmentioning
confidence: 99%